Implementasi Konsep â€œThe Common Learnerâ€ Pada Redesain Interior Perpustakaan Umum Kota Surabaya - Kurniawan, Vincensius Reynald; Sitinjak, Ronald Hasudungan Irianto; Suryanata, Linggajaya (Intra, 2018)
The Rungkut library is one of two Public Libraries available in Surabaya City. This building is supposed to be the main building of the Surabaya City Public Library, however, plenty of design, aesthetics, and facility problems instantly ruins that image. This needs to be fixed with a thorough redesign process.The library is redesigned through an analysis process, experimentation towards design schematics, and application of a new concept called â€œThe Common Learner.â€ This new concept focuses itself on three different things that are currently the main value of modern libraries, which is keeping productivity afloat, making people more enthusiastic inside the library, and adding comfort value for all visitors. This concept is used in the new design, and also adding new facilities the library needs, such as a computer area, self-service circulation machine, and multimedia collection with e-books.Through the redesign results, there are hopes that the citizen of Surabaya City can go back to visiting the Surabaya City Public Library building, and in turn, the library could fulfill the citizensâ€™ needs while also making the citizens develop reading habits.